PERILAKU CARING PERAWAT BERDASARKAN TIPE RUANGAN DI RUMAH SAKIT YANG TERAKREDITASI INTERNASIONAL DI BALI - Kusmadeni, Komang; Yanti, Ni Putu Emy Darma; Suarningsih, Ni Kadek Ayu (Coping: Community of Publishing in Nursing; Vol 12 No 4 (2024): Agustus 2024DO - 10.24843/coping.2024.v12.i04.p01, 2025)
Assessing caring behavior has now become a global issue, especially in the providers and recipients of nursing carezin the inpatientoroom. Thisostudy aimseto identify thennurse caring behavior based on the type of room in internationally accredited hospitals in Bali. This study accross-sectional designowith a totalosampling method. Nurse caring behavior data was collected using The Caring Behavior Inventory (CBI) instrument. The sample in this study was 88 respondents who were nurses. The results of the study get a description of caring behavior in each dimension based on a questionnaire or majority observation in either category. Whereas based on the type of questionnaire room and observation sheets, it was found that the room with the most caring nurse behavior was assessed by the questionnaire was pediatric care room (72.2%). This researchiis expectedeto be a foundation in developing programs to improve the quality of health workers, especially regarding caring behaviors of implementing nurses.